Rubus pseudoswinhoei (Rosaceae), a distinct new species from Yunnan, southwest China - Wang, Huan-Chong; Ma, Jing-Xia; He, Zhao-Rong (Phytotaxa, 2016)
Rubus pseudoswinhoei Huan C. Wang & Z. R. He, belonging to R. subg. Malachobatus sect. Sozostyli, is described and illustrated as a new species endemic to Yunnan, southwest China. The new species occurs in evergreen broad-leaved forests at elevations of 2500–2900 m. It is closely related to R. swinhoei Hance but clearly differs from the latter by its stipules usually persistent, 1.5–2 cm long, leaves with 12–18 pairs of lateral veins, pedicels 0.8–1.5 cm long, hypanthium 0.8–1.1cm in diameter, and sepals triangular-ovate to triangular-lanceolate, and 1–1.5 cm long. An up-to-date identification key to currently known species of Rubus sect. Sozostyli is provided.